Fluvial Export of Carbon and Nutrients from Boreal Catchments Disturbed by Fire and Permafrost Thaw - Tamara K. Harms; Alexandra J. Webster; Neal J. Pastick (Ecosystems, 2026)
Increased frequency and intensity of fire in the boreal forest can degrade permafrost and redistribute large pools of carbon and nitrogen that influence global climate. However, these changes are difficult to observe and predict at regional spatial scales and decadal or longer timescales. As receiving features of landscapes, streams integrate biogeochemical activity within the contributing area and might provide signals of disturbance and recovery at the catchment scale. We modeled solute concentrations as a function of fire history (0–100% catchment area burned less than one to > 79 years ago), permafrost, topography, and vegetation in 75 catchments of Interior Alaska. Concentrations of dissolved organic carbon (DOC) declined significantly with increasing proportion of the catchment burned, indicating that fire reduced stores of organic matter in the catchment, likely within the forest floor. We applied parameters estimated by regression models to predict that complete burning of catchments would reduce yield of DOC by an average of 46% (– 1.6 kg km –2 d –1 ) during the summer low-flow period. Solute concentrations were uninfluenced by time since fire, suggesting decadal-scale legacies of fire on fluvial exports or heterogeneous trajectories of ecosystem recovery following fire. Elevated concentrations of dissolved inorganic nitrogen in streams draining less extensive permafrost indicated potential for nitrogen export from catchments upon permafrost thaw. Concentrations of weathering products (e.g., sodium, chloride, sulfate) were weakly influenced by fire or permafrost extent, suggesting that disturbance primarily affected export of carbon, nitrogen, and phosphorus by reducing organic stocks and biological nutrient retention. Stream chemistry reflects the fire history and permafrost extent of boreal forest ecosystems, providing a spatially integrative indicator of ecosystem response and recovery from disturbance.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Differential endothelial cell cycle status in postnatal retinal vessels revealed using a novel PIP-FUCCI reporter and zonation analysis - Ziqing Liu; Natalie T. Tanke; Alexandra Neal; Tianji Yu; Tershona Branch; Arya Sharma; Jean G. Cook; Victoria L. Bautch (Angiogenesis, 2024)
Cell cycle regulation is critical to blood vessel formation and function, but how the endothelial cell cycle integrates with vascular regulation is not well-understood, and available dynamic cell cycle reporters do not precisely distinguish all cell cycle stage transitions in vivo. Here we characterized a recently developed improved cell cycle reporter (PIP-FUCCI) that precisely delineates S phase and the S/G2 transition. Live image analysis of primary endothelial cells revealed predicted temporal changes and well-defined stage transitions. A new inducible mouse cell cycle reporter allele was selectively expressed in postnatal retinal endothelial cells upon Cre-mediated activation and predicted endothelial cell cycle status. We developed a semi-automated zonation program to define endothelial cell cycle status in spatially defined and developmentally distinct retinal areas and found predicted cell cycle stage differences in arteries, veins, and remodeled and angiogenic capillaries. Surprisingly, the predicted dearth of S-phase proliferative tip cells relative to stalk cells at the vascular front was accompanied by an unexpected enrichment for endothelial tip and stalk cells in G2, suggesting G2 stalling as a contribution to tip-cell arrest and dynamics at the front. Thus, this improved reporter precisely defines endothelial cell cycle status in vivo and reveals novel G2 regulation that may contribute to unique aspects of blood vessel network expansion.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Low-dimensional trade-offs fail to explain richness and structure in species-rich plant communities - Alexandra Esther; Jürgen Groeneveld; Neal J. Enright; Ben P. Miller; Byron B. Lamont; George L. W. Perry; Britta Tietjen; Florian Jeltsch (Theoretical Ecology, 2011)

Pollination and other ecosystem services produced by mobile organisms: a conceptual framework for the effects of land‐use change - Claire Kremen; Neal M. Williams; Marcelo A. Aizen; Barbara Gemmill‐Herren; Gretchen LeBuhn; Robert Minckley; Laurence Packer; Simon G. Potts; T'ai Roulston; Ingolf Steffan‐Dewenter; Diego P. Vázquez; Rachael Winfree; et al. (Ecology Letters, 2007)
Many ecosystem services are delivered by organisms that depend on habitats that are segregated spatially or temporally from the location where services are provided. Management of mobile organisms contributing to ecosystem services requires consideration not only of the local scale where services are delivered, but also the distribution of resources at the landscape scale, and the foraging ranges and dispersal movements of the mobile agents. We develop a conceptual model for exploring how one such mobile‐agent‐based ecosystem service (MABES), pollination, is affected by land‐use change, and then generalize the model to other MABES. The model includes interactions and feedbacks among policies affecting land use, market forces and the biology of the organisms involved. Animal‐mediated pollination contributes to the production of goods of value to humans such as crops; it also bolsters reproduction of wild plants on which other services or service‐providing organisms depend. About one‐third of crop production depends on animal pollinators, while 60–90% of plant species require an animal pollinator. The sensitivity of mobile organisms to ecological factors that operate across spatial scales makes the services provided by a given community of mobile agents highly contextual. Services vary, depending on the spatial and temporal distribution of resources surrounding the site, and on biotic interactions occurring locally, such as competition among pollinators for resources, and among plants for pollinators. The value of the resulting goods or services may feed back via market‐based forces to influence land‐use policies, which in turn influence land management practices that alter local habitat conditions and landscape structure. Developing conceptual models for MABES aids in identifying knowledge gaps, determining research priorities, and targeting interventions that can be applied in an adaptive management context.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)